2015
DOI: 10.1074/jbc.m114.618769
|View full text |Cite
|
Sign up to set email alerts
|

Rewired Metabolism in Drug-resistant Leukemia Cells

Abstract: Background: Drug resistance is a common problem in cancer chemotherapy. Results: Transcriptomic and metabolomic data show that resistant leukemia cells exhibit reduced glutamine dependence, enhanced glucose dependence, and altered fatty acid metabolism. Conclusion:The metabolism of resistant leukemia cells is fundamentally rewired. Significance: Understanding the metabolic cost of resistance can lead to novel therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…Studies showed that carnitine and ALCAR levels are associated with type 2 diabetes and insulin resistance, suggesting that FAO plays a role in the pathogenesis of diabetes [24,25]. Claudia et al reported that drug-resistant human T-lymphoblastic leukemia (CEM) cells exhibited reduced levels of short-chain acyl carnitines, implying a reduction in the FAO rate [26]. Here, we found decreased levels of l-carnitine and ALCAR in BM cells of mice exposed to benzene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that carnitine and ALCAR levels are associated with type 2 diabetes and insulin resistance, suggesting that FAO plays a role in the pathogenesis of diabetes [24,25]. Claudia et al reported that drug-resistant human T-lymphoblastic leukemia (CEM) cells exhibited reduced levels of short-chain acyl carnitines, implying a reduction in the FAO rate [26]. Here, we found decreased levels of l-carnitine and ALCAR in BM cells of mice exposed to benzene.…”
Section: Discussionmentioning
confidence: 99%
“…Acaa2 was reported to be differentially expressed in CEM and drug-resistant leukemia cells [26]. Crot expression was found to be over-expressed in multidrug-resistant K562 leukemia cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…The linear gradient was 0 min, 5% B; 7 min, 95% B; 9 min, 95% B; 9.2 min, 5% B; 11 min, 5% B. MS data was collected in centroid mode between m/z 70-1700 using the following ESI settings: Gas Temp, 300; Gas Flow, 8; Nebulizer Pressure, 40; Sheet Gas Temp, 350; Sheet Gas Flow, 11; Vcap, 4000; Fragmentor, 100; Skimmer1, 45; OctapoleRFPeak, 750. The analysis procedure has also been described previously (Staubert et al 2015; Lindahl et al 2016). …”
Section: Methodsmentioning
confidence: 99%
“…As previously mentioned, CPT1α protein and mRNA levels both increase in alloreactive T cells during GVHD, and inhibition of CPT1α by etomoxir reduces alloreactive T cell proliferation and decreases disease severity [49]. Interestingly, inhibition of CPT1α by the small molecule ST1326 also decreases fatty acid oxidation and increases apoptosis in both leukemia cell lines and primary leukemia samples [104] and perhexiline, a CPT1α inhibitor approved for use in Australia [105], has shown anti-leukemia effects [106, 107]. The difficulty with many of these compounds is their serious side effect profiles [108], which for etomoxir includes cardiac hypertrophy and for perhexiline involves both neuro- and hepatotoxicity [109, 110].…”
Section: Therapeutic Targeting Of Metabolic Pathwaysmentioning
confidence: 99%